2011
DOI: 10.1007/s11418-011-0543-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening of promising chemotherapeutic candidates against human adult T-cell leukemia/lymphoma from plants: active principles from Physalis pruinosa and structure–activity relationships with withanolides

Abstract: Adult T-cell leukemia/lymphoma (ATL) is a peripheral T-cell malignancy caused by human T-cell lymphotropic virus type I (HTLV-1). Clinical manifestations of ATL range from smoldering to chronic, lymphoma and acute subtypes. Patients with acute and lymphoma-type ATL require therapeutic intervention. Conventional chemotherapeutic regimens used against other malignant lymphoma have been administered to ATL patients, but the therapeutic outcomes of acute and lymphoma-type ATL remain very poor. In this study, 214 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…After activity-guided fractionation against MT-1 and MT-2 cells, five active withanolides ( 93 – 97 ) were isolated from the aerial parts of Physalis pruinosa (Solanaceae) [ 32 ]. Structure–activity relationships suggested that the presence of a 5β, 6β epoxy group in the B-ring and a 4β-hydroxy group in the A-ring were important for the observed activities.…”
Section: Active Principlesmentioning
confidence: 99%
“…After activity-guided fractionation against MT-1 and MT-2 cells, five active withanolides ( 93 – 97 ) were isolated from the aerial parts of Physalis pruinosa (Solanaceae) [ 32 ]. Structure–activity relationships suggested that the presence of a 5β, 6β epoxy group in the B-ring and a 4β-hydroxy group in the A-ring were important for the observed activities.…”
Section: Active Principlesmentioning
confidence: 99%
“…Resazurin reduction assay is well known and has been employed in some studies to screen compounds for ATL treatment due its reliability to test cell proliferation and/or viability and evaluate anti-proliferative effect on MT-1 and MT-2 cell lines. 27 For instance, a range of plant extracts have been tested by this method to isolate components with potent inhibitory activity for further tests, 28,29 and YM155, an antitumor imidazolium compound and potent inhibitor of Survivin, was tested on a variety of human cancer cell lines, including T-acute lymphoblastic leukemia (T-ALL). 30 The initial screening on HTLV-1-infected cell line (MT-2) led us to select eight compounds (02, 05, 06, 13, 15, 21, 22 and 25) (Figure 2) for further studies as they significantly reduced the metabolic activity of the cells (≥ 70%) in a similar manner to the positive control (ETO).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolite production in a host plant can also be triggered by the existence of a parasite, as discussed in a study on Tapirira guianensis infested by Phoradendron perrottetii, in which infested branches produced more tannin compare to non-infested branches, with infestation inducing a systemic response [48]. Against T-cell leukemia [197], antimicrobial [198] 111…”
Section: Epiphytic Plant-host Interactions On Secondary Metabolite Tamentioning
confidence: 99%